Silicon mitigates ammonium toxicity in plants - Campos, Cid Naudi Silva (2020)
The search for high yield has identified ammonium toxicity as a problem in arable soils world wide. Ammonia toxicity can be suppressed by the use of silicon, but this fact still needs to be elucidated. Therefore, this review aimed to highlight the harmful effects of ammonium toxicity on model plants, and to determine the effects of Si on the mitigation of abiotic stress. Some plant species are considered as tolerant, and others as sensitive to high N concentrations. In sensitive plants, high ammonium concentrations may hinder the plant's development and even lead to the plant's death due to biochemical, physiological, and nutritional changes. Studies have demonstrated that silicon can mitigate or alleviate the deleterious effects caused by the toxic effect of NH4 +. These findings were attributed to improvements in the physiological and nutritional parameters of plants. Given the importance of ionic balance between N forms for the plant's development, further studies must be performed to detect mechanisms promoted by Si to decrease or mitigate the harmful effects caused by excess ammonium in plants.